Shigeru Ban : complete works, 1985-2015 - Jodidio, Philip; Ban, Shigeru, 1957-; Jodidio, Philip; Jodidio, Philip; Jodidio, Philip (Köln : Taschen, 2015)
"This updated monograph, compiled with the architect's collaboration, brings together every one of Ban's built works, including such recent projects as the Madrid Paper Pavilion, the Aspen Art Museum, and the Cardboard Cathedral in Christchurch."
Includes bibliographical references.
ARC
Text in English, French, and German.
Keywords: Ban, Shigeru, -- 1957- -- Catalogs; Architecture -- Japan -- History -- 20th century -- Catalogs; Architecture -- Japan -- History -- 21st century -- Catalogs; Architecture